Performance investigation of graphene based-nanofluids as a metalworking fluid for turning process - Talib, Norfazillah; Mohd Azmi, M. K. E.; Jamaluddin, Nor Athira; Woon, Kiow Lee; Abdullah, Haslina; Ahmad, Said; Saleh, Aslinda (2023)
Most lubricants used for machining industry are mineral-based oil thus gives negative impact on environment and humans because of their toxicity and non-biodegradability. Therefore, vegetable-based oil has been taken as other initiatives to produce bio-based metalworking fluid (MWFs) especially from non-edible oil (jatropha oil). The aim of this study was to investigate the turning performance of nanofluids from modified jatropha based-oil (MJO) with the addition of graphene nanoparticles at various concentrations (0.01wt%, 0.025wt%, 0.05wt%). The performances of MJO based nanofluids were compared with synthetic ester (SE) as the benchmark oil in terms of cutting temperature, chip thickness and workpiece surface roughness. From the results, MJO + 0.025wt% graphene nanoparticles recorded the lowest cutting temperature, and chip thickness with smoother workpiece surface roughness compared to all samples. In conclusion, MJO + 0.025wt% exhibit superior machining performance and could be potential candidate as sustainable MWFs to replace mineral based oil for the machining processes